Great Events: Indicators for Classification and their Impact on the Urban Systems - Mazzeo, Giuseppe (TeMA - Journal of Land Use, Mobility and Environment, 2008)
Great Events are an opportunity for the cities because they are an extraordinary catalyser of investments for the transformation of the city. The action of the great events is not confined only in the period of the event but it extends before it and, more and more, after the end of it. In the more recent events the transformation of the city has interested the urbanized parts of it and has become the occasion for transforming the built city and modifying the profile of a city. The paper deepens the question of the event’s classification and of their impact on the urban system. It is organized in three parts. The first part analyses two types of great events (the international expositions and the Olympic games) with the aim to characterize a shared definition. The second part identifies the more important factors and indicators for to analyze the category of the great events. The last part is based on the factors impacting on the urban system and on the organization of its mobility. In particular, the concept of “pulsar effect” is deepen: it is the multiplicative effect on a city evolution in relation to the organization of sequential or parallel multiple events. One of the more negative impact of a great event is the dissipation of the benefits in the time for the lack of other events. In this way the city loses the acquired advantages and return in the same pre-event state. For preserving the advantages it is necessary to strengthen the acquired position with other events.